Om Regner Birkelunds Grundtvig-disputats - Schjørring, Jens Holger (Dansk Teologisk Tidsskrift, 2009)
Regner Birkelund defended his thesis “Freedom for the Common – An oppositional voice from the past” for the philosophical doctoral degree at Aarhus University on October 31, 2008. The thesis explores N.F.S. Grundtvig’s concept of freedom from an interdisciplinary perspective. Birkelund rejects simplistic interpretations in case they associate Grundtvig with either liberalistic or socialist ideologies. At the same time Birkelund examines a range of areas within Grundtvig’s writings such as his historical and philosophical essays on modern and contemporary society, his articles about education and school reform, his political writings and his contributions on the emancipation of women and female values and their relationship with the biblical sources of Christianity. Birkelund sets out to investigate the inspiration which Grundtvig gained from classical Greek culture. Adding to Grundtvig’s rootedness in ancient ideas Birkelund also wants to demonstrate that Grundtvig was a forerunner for a balanced interaction in contemporary society between the struggle for freedom and the concern for justice and the common good. The article presents a summary of the lectures of opposition held during the defense by Harry Haue, Dag Thorkildsen, Ole Vind and Jens Holger Schjørring.